Presidential Election Dispute Resolutionin the Fiqh Siyasah Perspective - Anisa, Lina Nur (International Journal of Islamic Studies Issues, 2025)
This article discusses the resolution of presidential election disputes from the perspective of fiqh siyasah. This research applies a qualitative approach with library research as its method. The data collection technique employed is documentation, accompanied by data analysis techniques such as content analysis, induction, and deduction. The findings of this discussion indicate that integrating fiqh siyasah into modern politics is crucial, especially in Muslim-majority countries or those implementing Islamic principles in governance. Fiqh siyasah, emphasizing justice, transparency, accountability, and the common good, provides an ethical framework that can enhance the quality of democracy and the political process. This is relevant when facing modern politics, which is often rife with conflicts of interest. By basing policies on fairness and transparency, the government will be more just, more respected, and hold stronger legitimacy. Such policies also support social stability and harmony. In resolving presidential election disputes, fiqh siyasah acts as a guide in election audits and conflict resolution. The principles of shura and maslahah (public interest) help find solutions that benefit the entire society, reduce political tensions, and strengthen public trust in the democratic process.